Various English Literacy Activities in Bilingual Primary School - Puspitasari, Putu Indah; Padmadewi, N.N.; Dewi, L.P.E.S. (International Journal of Elementary Education, 2021)
The results of Program of International Student Assessment show that the literacy skills of Indonesian students was in the low level. This study aims to investigate English literacy activities in elementary schools. This research is a qualitative research with a case study method. There were three English teachers who teach on the 1st, 2nd, and 3rd grade assigned as the subjects of this study.  Data were collected using a questionnaire, interview guide, and checklist. The data collection procedure was carried out by distributing questionnaires, conducting interviews, and conducting classroom observations. Data were analyzed using data analysis methods from Cresswell which consisted of data organization, coding, description and developing themes, reporting findings, interpreting, and validating data. The results of this study indicate that there are eight literacy activities, namely Directed Reading-Thinking Activity, guided reading, reading with multimedia assistance, thinking aloud, reading aloud, dictating, recognizing letters, and writing. This study provides a description about English literacy activities in Primary School conducted by teachers. Therefore, a suggestion is directed to English teachers to teach literacy to students since the early age as literacy is an important basis for students’ future learning.